1997
DOI: 10.1007/s001340050335
|View full text |Cite
|
Sign up to set email alerts
|

Mortality discrimination in acute myocardial infarction: comparison between APACHE III and SAPS II prognosis systems

Abstract: The results indicate good discrimination by the three tests. APACHE III probability shows a statistically significant improvement in accuracy and specificity when compared with the two scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
1
12
1
3
Order By: Relevance
“…Patients with acute myocardial infarction had a hospital mortality of 15.6 %. This is in the range of earlier reports with mortality figures from 13 % [15] to 16 % [8].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Patients with acute myocardial infarction had a hospital mortality of 15.6 %. This is in the range of earlier reports with mortality figures from 13 % [15] to 16 % [8].…”
Section: Discussionsupporting
confidence: 72%
“…Reina et al [15] investigated the recent versions of both scores (APACHE III, SAPS II) in a prospective multicenter study of 1711 patients with acute myocardial infarction. They calculated severity, specificity, and accuracy or mortality discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, Reina et al [35] showed much low er mean values on admission for SAPS II in survivors and nonsurvivors (33.3 and 49.2, respectively). This demonstrates the difference between AMI and AMI leading to CS and also the high mortality of CS.…”
Section: Scoring In Cardiogenic Shockcontrasting
confidence: 99%
“…Knaus et al [23] studied 17,740 patients and showed an AUC of 0.90 on admission and an aver age admission score of 50 points for the APACHE III. In a study by Reina et al [35] of 1,711 patients with AMI, the AUC was 0.84 with a sensitivity of 75.80 and a specificity of 75.90. In 2001, Markgraf and coworkers [26] showed an AUC of 0.846 for APACHE III in 1,772 interdiscipli nary ICU patients.…”
Section: Scoring In Cardiogenic Shockmentioning
confidence: 92%
“…The most frequent causes of admission were acute myocardial infarction and unstable angina (1,757 and 724 patients, respectively); COPD was the cause of admission for 508 patients, although more patients (742 of the 8,685 total) presented with COPD. This project studied the characteristics (severity, diagnosis, resource consumption, and QOL) of patients admitted to ICUs in Spain and has given rise to published articles addressing the evaluation and Spanish adaptation of the APACHE III in Spain (27,28), comparison of the APACHE III and the Simplified Acute Physiology Score (SAPS II) systems in acute myocardial infarction (29), correlation between the Therapeutic Intervention Scoring System (TISS) and TISS 28 (30), study of therapeutic activity by patient age (31), validation of a specific QOL questionnaire for critical care patients (14), and assessment of QOL of patients before ICU admission and its influence on hospital mortality (15).…”
Section: Methodsmentioning
confidence: 99%